"A friend gave me a phone number" – Brokerage in low-level corruption. Issue 1 (March 2015) - Jancsics, David
Abstract Corrupt exchanges are often brokered by a third party, but this phenomenon has not been satisfactorily explored by researchers of corruption. Literature on brokerage in general provides interesting models but they have not previously been applied to corrupt exchanges. Based on in-depth qualitative interviews with respondents who participated in actual corrupt transactions, this paper identifies several distinct brokerage types in low-level corruption in contemporary Hungary. The paper also provides explanation of variation in corruption brokerage in terms of actors' group affiliations, forms of the corrupt exchanges, brokerage mechanisms, as well as neutrality, benefit and motivation, risk distribution, and stability of the brokerage structure. Finally, we discuss some policy implications of corruption brokerage.